The Effect Of Dual Role Conflict On Marital Satisfaction Moderated By Emotional Regulation In Young Married Couples In The Special Region Of Jakarta - Imara, Analisa; Roswiyani, Roswiyani; Satiadarma, Monty P. (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study examines the influence of dual role conflict on marital satisfaction among young married couples in Jakarta, with emotion regulation as a moderating variable. The background of this research lies in the increasing demands of household roles, especially for couples who both work. Dual role conflict arises when individuals face pressure to fulfill multiple roles simultaneously, such as being a spouse, a parent, and a professional. This study employed a quantitative approach using a survey method involving 200 participants aged 20–40 years who were already married. The majority of participants were women who actively worked and carried out multiple roles in their daily lives. The instruments used included the Role Conflict Scale to measure dual role conflict, the Emotion Regulation Questionnaire (ERQ) to measure emotion regulation, and the Enrich Marital Satisfaction Scale (EMSS) to measure marital satisfaction. Data analysis was conducted using moderation regression to determine whether emotion regulation strengthens or weakens the relationship between dual role conflict and marital satisfaction. The results showed that dual role conflict had a significant negative effect on marital satisfaction. However, emotion regulation was found to moderate this relationship. Individuals with strong emotion regulation skills were more capable of managing role pressures and maintaining the quality of their marital relationships. These findings highlight the importance of emotion regulation training as an adaptive strategy, particularly for working women. The practical implications are directed toward counselors, psychologists, and policymakers in providing support for married couples in the modern era.